The effectiveness of online Eye Movement Desensitization and Reprocessing 2.0 Group Protocol on post-traumatic stress disorders symptoms, depression, anxiety, and stress in individuals who have experienced a traffic accident: a randomized-controlled study - Yasar, Alişan Burak; Gundogmus, İbrahim; Kubilay, Derin; Alban Tunca, Görkem; Uygun, Ersin; Zat Çiftçi, Zeynep; Kavakcı, Önder (Frontiers in Psychiatry, 2025)
IntroductionEMDR 2.0, an innovative approach rooted in the conventional Eye Movement Desensitization and Reprocessing (EMDR), has garnered attention due to its promising outcomes. The application of EMDR, whether it is EMDR or EMDR 2.0 protocol, in a group format, especially for conditions like Post-Traumatic Stress Disorder, will provide significant opportunities in terms of economic feasibility and accessibility, ultimately leading to widespread use. Building on the established effectiveness of EMDR 2.0 in individual applications, this study examines its impact in group settings. This protocol is designed to provide a structured framework for implementing EMDR 2.0 within group contexts, paving the way for a nuanced understanding of its potential benefits in collective therapeutic settings. This study aims to investigate the efficacy of the online EMDR 2.0 Group Protocol(EMDR 2.0 GP) versus Improving Mental Health Training for Primary Care Residents(mhGAP) on individuals with a history of traffic accidents in a controlled way.MethodsIn this randomized-controlled study sample includes volunteers who were involved in traffic accidents and were given the randomized online EMDR 2.0 GP and mhGAP Stress management module. The participants were given a sociodemographic data form, Depression Anxiety Stress 21 scale (DASS-21) and Impact of Event Scale-Revised (IES-R). Participants were evaluated with measurements before, after and “one month after the application.ResultsThe mean age of the participants was 34.80(8.10) years and 88.0% (n=22) were female. The change in DASS-21 Anxiety (h2=0.136), Stress (h2=0.140), IES-R Avoidance (h2=0.134), Hyperarousal (h2=0.0148), Total (h2=0.223) scores of online EMDR 2.0 GP was determined to be statistically significant compared to the mhGAP group. However, no statistically significant difference was observed in DASS-21 Depression (h2=0.017), IES-R Intrusion(h2=0.094), scores between the two groups.DiscussionThe RCT of online EMDR 2.0 GP indicated that this newly developed protocol, when applied to groups, may be effective in reducing anxiety, stress, and traumatic symptoms among a non-clinical sample.Clinical trial registrationhttps://clinicaltrials.gov/study/, identifier NCT05596903.